Rotation‐restricted strategy to synthesize high molecular weight polyethylene using iminopyridyl nickel and palladium catalyst. (28th December 2020) - Peng, Hongwei; Li, Shuaikang; Li, Gen; Dai, Shengyu; Ji, Mingjun; Liu, Zhe; Guo, Lihua
Abstract : Most of the iminopyridyl Ni (II) and Pd (II) catalysts are reported to oligomerize ethylene or yield very low molecular weight polyethylene. Moreover, the molecular weight of product is not sensitive to ligand sterics. In this contribution, we demonstrate that the bulky rotation‐restricted substituents incorporated into iminopyridyl Ni (II) and Pd (II) catalysts that provide the right orientation are highly effective in retarding the chain transfer. Thus, (2, 6‐bis(10, 11‐dihydro‐5 H ‐dibenzo[ a, d ][7]annulen‐5‐yl)‐4‐methylphenyl)‐1‐(pyridin‐2‐yl)methanimine nickel (II) bromide (Ni3 ) and (2, 6‐bis(10, 11‐dihydro‐5 H ‐dibenzo[ a, d ][7]annulen‐5‐yl)‐4‐methylphenyl)‐1‐(pyridin‐2‐yl)methanimine palladium (II) methyl chloride (Pd3 ) with the phenyl substituents fixed in the diarylmethyl moiety produce polyethylene or functionalized polyethylene (ethylene‐MA copolymer) with high M n values up to 2.5 × 10 4 g mol −1, while allowing the high MA incorporation (3.2%–13.8%). In addition, the effects on the (co)polymerization behavior as a function of rotation‐restricted substituent variations (free rotation, restricted rotation and fixation) were systemically studied. As a result, various molecular weight polyethylene and ethylene‐MA copolymer with high MA incorporation ratio were also obtained in this system. Abstract : Synopsis: The bulky rotation‐restricted substituents incorporated into iminopyridyl Ni(II) and Pd(II) catalysts that provide the right orientation are highly effective in retarding the chain transfer and thus produce high molecular weight polyethylene.